Daur at-Tiknūlūjiyā ar-Raqmiyyah fī Ta‘līm al-Lughah al-‘Arabiyyah fī Indūnīsiyā: Dirāsah Tārīkhiyyah wa Naw‘iyyah wa Fawā’idiyyah: - Syamsul Hadi; Syamfa Agny Anggara (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2026)
In this digital era, technology has infiltrated all aspects of our life, including the field of learning process. the rapid advancement of technology has had a significant impact on the methods of Arabic language learning. The use of digital technology in Arabic language learning has become a necessity to achieve better learning quality and effectiveness in the learning process. The purpose of this research is to explore the role of digital technology in Arabic language learning in Indonesia from historical, typological, and functional perspectives. The study employs a qualitative approach using library research, through a comprehensive analysis of books, journal articles, and educational reports related to Arabic digital learning. The findings based on the synthesis of these scholarly sources show that the use of digital technology in Arabic language learning has evolved historically from visual aids and basic media into interactive and AI-based learning platforms. In addition, various types of technologies contribute differently to improving the quality of learning, enriching student engagement, facilitating access to information, and enhancing comprehension. Overall, digital technology plays an essential role in modernizing Arabic language learning in Indonesia and continues to drive innovation in the field.